Model predictive control applied to an improved five-level bidirectional converter - Monteiro, Vítor Duarte Fernandes (2016)
This paper presents an improved five level bidirectional converter (iFBC) controlled by finite control set model predictive control (FCS-MPC). This control strategy consists in using the discrete time nature of the iFBC to define its state in each sampling interval. Using FCS-MPC the switching frequency is not constant; however, it is suitable to follow the current reference with low total harmonic distortion (THD). The iFBC prototype that was specially developed for obtaining experimental results is described in detail along the paper, as well as its principle of operation, power theory, and current control strategy. The iFBC was experimentally validated connected to the power grid through a second order LfCf passive filter, operating as an active rectifier and as a grid tie inverter. For both operation modes, the experimental results confirm the good performance (in terms of efficiency, low current THD and controlled output voltage) of the iFBC controlled by FCS-MPC.